Genomics and Public Health: Development of Web-based Training - Janice V. Bach, MS; Aaron Goldenberg, MA, MPH; Toby Citrin, JD; Sarah F. Raup, MPH; Jennifer Bodzin, MPH; Sharon L.R. Kardia, PhD (Centers for Disease Control and Prevention, 2005)
In 2001, the Centers for Disease Control and Prevention funded three Centers for Genomics and Public Health to develop training tools for increasing genomic awareness. Over the past three years, the centers, working together with the Centers for Disease Control and Preventions Office of Genomics and Disease Prevention, have developed tools to increase awareness of the impact genomics will have on public health practice, to provide a foundation for understanding basic genomic advances, and to translate the relevance of that information to public health practitioners own work. These training tools serve to communicate genomic advances and their potential for integration into public heath practice. This paper highlights two of these training tools: 1) Genomics for Public Health Practitioners: The Practical Application of Genomics in Public Health Practice, a Web-based introduction to genomics, and 2) Six Weeks to Genomic Awareness, an in-depth training module on public health genomics. This paper focuses on the processes and collaborative efforts by which these live presentations were developed and delivered as Web-based training sessions.